Foreign Language Mediation Activities in the Dialogue of Cultures - E. V. Voevoda (Vestnik MGIMO-Universiteta)
The article addresses the CEFR extended set of language proficiency descriptors. The author points out that education, as well as the language, make an integral part of national culture and reflect the problems existing in society including the problems in communication and social interaction. In the early 21st century the process of communication became largely monolingual with English as the global lingua franca. The Bologna process contributed to building the European education environment based on the principle of multilinguism, which implies that representatives of different ethnic groups with different mother tongues communicate in the same language within a single social group. In 2001, in order to synchronize the national curricula, the Council of Europe adopted CEFR - Common European Framework of Reference for Languages: Learning, Teaching, Assessment which presents descriptors of the six levels of language proficiency. Ten years later it became evident that the descriptors needed to be revised. While economies were converging, cultures began to diverge. Globalization made Europeans realize the value of every single ethnic culture. That led to the idea of plurolinguism which argues that an individual can communicate in a variety of languages using a variety of language forms known to them. The process of communication thus calls for mediation activities that facilitates communication if the interlocutors are unable to understand each other directly. That means that the aim of language learning changes from perfecting a certain foreign language to building plurilingual and pluricultural competences.